MEMAKNAI TRADISI KOFAN AOF MAPUTU SEBAGAI SUATU TANDA KESELAMATAN DAN PENGARUHNYA TERHADAP PERKEMBANGAN IMAN SUKU MATUA - Sako, Delviana; Habu Lelo, Elmagondulfa; Kono, Videl Remus (Kanisius, 2025)
This study aims to determine the meaning of the Kofan Aof Maputu traditionfor the Matua tribe and how the Kofan Aof Maputu tradition influences the development of the Matua tribe’s faith. This research was conducted in Letneo Village, Insana Barat District, 2024 using qualitative research methods. The data collection techniques in this study were that the researcher used observation and interviews. Kofan Aof Maputu is one of the traditions that has been lived by the Matua tribe which is a cultural heritage left by their ancestors. As a legacy of their ancestors, the Matua tribe has a sense of responsibility to maintain and preverse this tradition. This tradition is carried out specifically for a mother who has just experienced the birth process for the first time. Literally, Kofan Aof Maputu means throwing away hot ash. In the Matua tribe tradition, a mother who hast just given birth is usually associated with activities that use materials containing hot elements; for example: bathing using hot water, always warming herself near a hot fire. Therefore, a ritual must be carried out to free the mother from activities that contain hot elements. There results of the study show that the Kofan Aof Maputu tradition has the meaning of safety for a mother who has just given birth for the first time. The safety in question is that the mother is restored and freed from all activities that contain elements of heat. Thus the mother can carry out daily routines and activities like other people, and is no longer bound by the elements of heat as intended during a mother’s rest period after giving birth. Maputu is also interpreted as something that always interferes with human life that can cause disaster for someone. Therefore, the mother and the newborn child must be freed from Maputu (disaster) so that they obtain manikin-oetene, aomina aoleko (peace and prosperity of the body and soul)